Odontogenic Keratocyst Looks Can Be Deceptive, Causing Endodontic Misdiagnosis - K. M. Veena; Rekha Rao; H. Jagadishchandra; Prasanna Kumar Rao (Case Reports in Pathology)
Odontogenic keratocyst (OKC) is the cyst arising from the cell rests of dental lamina. It can occur anywhere in the jaw, but commonly seen in the posterior part of the mandible. Radiographically, most OKCs are unilocular when presented at the periapex and can be mistaken for radicular or lateral periodontal cyst. When the cyst is multilocular and located at the molar ramus area, it may be confused to ameloblastoma. Lots of cases have been reported in the literature where OKC is associated with the nonvital tooth. So trauma could be one of the reasons in inducing this cyst. In our case, it was in the anterior region at the periapex of nonvital tooth having traumatic occlusion. Hence, the diagnosis of radicular cyst was made and endodontic treatment was done.